Bibliometric Trends in Social Media and Destination Marketing: Shaping Perceptions in the Tourism Industry - Judijanto, Loso; Suharto, Bambang; Susilo, Anton (Westscience Press, 2024)
This study delves into the transformative role of social media in tourism marketing, examining how these digital platforms influence traveler engagement and destination branding. Drawing from a comprehensive bibliometric analysis, the research synthesizes findings from seminal studies to explore the utilization of social media by tourism organizations and the resultant impact on traveler behavior and decision-making processes. The analysis highlights the strategic use of social media for enhancing destination attractiveness, the integration of big data to optimize marketing strategies, and the pivotal role of user-generated content in shaping destination images. The study identifies key trends, including the shift towards more personalized, interactive marketing approaches and the increasing reliance on technological innovations to drive marketing efficiency and effectiveness. These findings provide actionable insights for tourism marketers aiming to leverage social media's full potential within the dynamic digital landscape.